2020
DOI: 10.21203/rs.3.rs-45042/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association between ambient temperature and mortality of the coronavirus disease 2019 (COVID-19) in Wuhan, China: A time-series analysis

Abstract: BackgroundThe COVID-19 has caused a sizeable global outbreak and has been declared as a public health emergency of international concern. Sufficient evidence shows that temperature has an essential link with respiratory infectious diseases. The objectives of this study were to describe the exposure-response relationship between ambient temperature, including extreme temperatures, and mortality of COVID-19.MethodsThe Poisson distributed lag non-linear model (DLNM) was constructed to evaluate the non-linear dela… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…However, cancer detection rate per procedure was significantly increased from 1.91% in the pre-pandemic period to 6.61% during the COVID-19 period (8). Likewise, in two separate studies from China, although a considerable reduction in the endoscopic activity was found during the pandemic, there was a significantly greater percentage of patients diagnosed with malignancy (9,10). In a study comparing the 6-month period from the beginning of the pandemic in the UK (April to October 2020) to the same period of the previous year, it was shown that colonoscopies performed across the country dropped by 46% and colorectal cancer diagnosis was missed in over 3500 patients.…”
Section: Discussionmentioning
confidence: 93%
“…However, cancer detection rate per procedure was significantly increased from 1.91% in the pre-pandemic period to 6.61% during the COVID-19 period (8). Likewise, in two separate studies from China, although a considerable reduction in the endoscopic activity was found during the pandemic, there was a significantly greater percentage of patients diagnosed with malignancy (9,10). In a study comparing the 6-month period from the beginning of the pandemic in the UK (April to October 2020) to the same period of the previous year, it was shown that colonoscopies performed across the country dropped by 46% and colorectal cancer diagnosis was missed in over 3500 patients.…”
Section: Discussionmentioning
confidence: 93%
“…One of reasons why China's CFR is so high may be that people knew little about the virus early in the epidemic. The studies on the determinants of China's COVID-19 mortality focus more on the individual level from patients' perspective in Wuhan of Hubei Province [28,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%